AN ANALYSIS OF MAGIC SPELLS IN HARRY POTTER AND THE HALF-BLOOD PRINCE - Siti Ayu Mardiah Nduru (STBA Prayoga Padang, 2021)
Abstract This research aims to analyze the magic spells uttered by the characters in Harry Potter and The Half-Blood Prince movie and identify the meaning and functionsof the magic spells in the movie. To come to the analysis, the writer applied literal meaning and non-literal meaning based on Griffiths’s theory. Meanwhile, thefunction of magic spells analyzes based on Searle's theory. This research employed qualitative research and descriptive method. The data were collected by the nonparticipant method and taking notes, selecting dialogues containing magic spells while watching the video. The result finally found the functions of each spell and its meaning, whether it has literal or non-literal meaning.